The long-term trend of Parkinson’s disease incidence and mortality in China and a Bayesian projection from 2020 to 2030 - Chen, Fangyao; Chen, Shiyu; Si, Aima; Luo, Yaqi; Hu, Weiwei; Zhang, Yuxiang; Ma, Jiaojiao (Frontiers in Aging Neuroscience, 2022)
Background: Parkinson's disease is a disabling degenerative disease of the central nervous system that occurs mainly in elderly people. The changes in the incidence and mortality of Parkinson’s disease at the national level in China over the past three decades have not been fully explored. Methods: Research data were obtained from the Global Burden of Disease 2019 study. The trends of crude and age-standardized incidence and mortality rates by gender of Parkinson’s disease in China were analyzed with the age-period-cohort model and the Joinpoint regression analysis. The effects of age, time period, and birth cohort on the incidence and mortality of Parkinson’s disease were estimated. The gender- and age-specific incidence and mortality rates of Parkinson’s disease from 2020 to 2030 were projected using the Bayesian age-period-cohort model with integrated nested Laplace approximations. Results: From 1990 to 2019, the annual percentage change of the age-standardized incidence rate was 0.8% (95%CI: 0.7%~0.8%) for males and 0.2% (95% CI, 0.2–0.2%) for females. And the age-standardized mortality rate for males was 2.9% (95%CI: 2.6%~3.2%) and 1.8% (95%CI: 1.5%~2.1%) for females. The results of the age-period-cohort analysis suggested that the risk and burden of Parkinson’s disease continued to increase for the last several decades. Projection analysis suggested that the overall Parkinson’s disease incidence will continue to increase for the next decades. It was projected to be 4.787 million Parkinson’s patients in China by the year 2030, however, the mortality of Parkinson’s disease for both genders in China may keep decreasing. Conclusion: Though the mortality risk may decrease, Parkinson’s disease continues to become more common for both genders in China, especially in the senior-aged population. The burden associated with Parkinson’s disease would continue to grow. Urgent interventions should be implemented to reduce the burden of Parkinson’s disease in China.